2019
DOI: 10.1101/513390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No trace of phase: Corticomotor excitability is not tuned by phase of pericentral mu-rhythm

Abstract: Background: The motor potentials evoked by transcranial magnetic stimulation (TMS) over the motor hand area (M1-HAND) show substantial inter-trial variability. Pericentral murhythm oscillations, might contribute to inter-trial variability. Recent studies targeting muactivity based on real-time electroencephalography (EEG) reported an influence of mupower and mu-phase on the amplitude of motor evoked potentials (MEPs) in a preselected group with strong pericentral mu-activity. Other studies that determined mu-p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 47 publications
5
22
1
Order By: Relevance
“…Larger MEP amplitudes were found when TMS was administered at the trough compared to when it was administered at the peak of the mu-oscillation [31][32][33] (but see ref. 34 ). Others investigated the role of mu-power on MEP amplitude, suggesting that sensorimotor mu-power may reflect a net facilitation or disinhibition of M1 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Larger MEP amplitudes were found when TMS was administered at the trough compared to when it was administered at the peak of the mu-oscillation [31][32][33] (but see ref. 34 ). Others investigated the role of mu-power on MEP amplitude, suggesting that sensorimotor mu-power may reflect a net facilitation or disinhibition of M1 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The corticospinal response (measured by MEP) elicited by single-pulse TMS on M1 varies between trials[2730]. Recent studies have shown that this variability is associated with neural oscillation power[3137], phase[26,38,39], or their interaction[40], although one study failed to replicate these findings[41]. In our study, we showed that pre-stimulus mu-rhythm oscillatory power was correlated with the modulation of cortical and corticospinal excitability (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies seem to support the gating-through-inhibition hypothesis and report associations between low mu-power and higher MEP amplitudes [13e15], but these findings could not be replicated by a number of often better-powered studies [16e21] (See Ref. [22] for a detailed, tabular report of studies grouping MEPs according to prestimulus power). Real-time EEG-triggered stimulation systems makes it possible to assess the relationship between mu-oscillatory activity and MEP amplitude more effectively through online targeting of specific oscillation states [13e15].…”
Section: Introductionmentioning
confidence: 99%